Originary tmporality in being and time - Abdel Kader, Mai (AUC Knowledge Fountain, 2016)
Originary temporality is a pivotal concept in Heidegger’s Being and Time. Heidegger proposes that originary temporality is the basis for all forms of time. He argues that our ordinary explanation of time is given in terms of originary temporality because the moments which make up ordinary time are modified versions of the features of originary temporality. The seemingly controversial point in Heidegger’s interpretation of time lies in his conclusion that the mode of temporality that is appropriate for the interpretation of Dasein’s Being is a “non-sequential” one. This non-sequential temporality, or “originary” temporality, is not a mode of time where the past comes before the present which is followed by the future. Originary temporality is a temporal manifold that can be present in any moment of sequential time. In other words, it is a mode of time where the future, past, and present are all there at every given moment. The main goal of this research is to present an account of originary temporality in Heidegger’s philosophy, and to assess whether this form of temporality is a literal form of time or if it is only metaphorically so. I will argue that originary temporality as a non-sequential form of time that forms a unity is a real form of time, not just a metaphorical one.